Correction to: Sequencing and curation strategies for identifying candidate glioblastoma treatments - Mayu O. Frank; Takahiko Koyama; Kahn Rhrissorrakrai; Nicolas Robine; Filippo Utro; Anne-Katrin Emde; Bo-Juen Chen; Kanika Arora; Minita Shah; Heather Geiger; Vanessa Felice; Esra Dikoglu; et al. (BMC, 2019)
Following publication of the original article [1], it was reported that the given name of the fourteenth author was incorrectly published. The incorrect and the correct names are given below.